Plant and microbial community composition jointly determine moorland multifunctionality. (17th August 2022) - Sasaki, Takehiro; Ishii, Naohiro I.; Makishima, Daichi; Sutou, Rui; Goto, Akihito; Kawai, Yutaka; Taniguchi, Hayami; Okano, Kunihiro; Matsuo, Ayumi; Lochner, Alfred; Cesarz, Simone; Suyama, Yoshihisa; et al.
Abstract: Understanding how ecosystem multifunctionality is maintained in naturally assembled communities is crucial, because human activities benefit from multiple functions and services of various ecosystems. However, the effects of above‐ and below‐ground biodiversity on ecosystem multifunctionality in alpine and boreal moorland ecosystems remain unclear despite their potential as global carbon sinks. Here we evaluated how ecosystem multifunctionality related to primary production and carbon sequestration, which are crucial for global climate regulation, is maintained in natural systems. We disentangled the relationships between diversity and composition of plants and soil microbes (fungi and bacteria) and ecosystem multifunctionality in subalpine moorlands in northern Japan. We found that microbial composition primarily regulated carbon sequestration, whereas plant taxonomic and functional composition were related to all functions considered. Plant and microbial α diversity (diversity within local communities) were not generally related to any single function, highlighting the important roles of specific plant and microbial taxa in determining ecosystem functioning. When single functions were aggregated to ecosystem multifunctionality within local communities, plant and microbial community composition rather than diversity regulated ecosystem multifunctionality. We further found that plant and bacterial taxonomic β diversity (taxonomic turnover between local communities) primarily regulated the dissimilarity of ecosystem multifunctionality between local communities. Synthesis. We provide observational evidence that plant and microbial community composition rather than diversity are essential for sustaining subalpine moorland multifunctionality. Furthermore, plant and bacterial β diversity enhance the dissimilarity of moorland multifunctionality. Our study provides novel insights into biodiversity–ecosystem multifunctionality relationships occurring in nature, and helps to sustain desirable ecosystem functioning to human society. Abstract : Here, we disentangled the relationships between diversity and composition of plants and soil microbes (fungi and bacteria) and ecosystem multifunctionality in subalpine moorlands in northern Japan. Natural variations in plant and microbial community composition, rather than diversity, are essential for sustaining moorland multifunctionality. Furthermore, plant and bacterial β diversity have large effects on the dissimilarity of moorland multifunctionality between communities.